Recent Advances in Halide Perovskite Resistive Switching Memory Devices: A Transformation from Lead-Based to Lead-Free Perovskites - Thien G.S.H.; Ab Rahman M.; Yap B.K.; Tan N.M.L.; He Z.; Low P.-L.; Devaraj N.K.; Ahmad Osman A.F.; Sin Y.-K.; Chan K.-Y. (American Chemical Society, 2023)
Due to their remarkable electrical and light absorption characteristics, hybrid organic-inorganic perovskites have recently gained popularity in several applications such as optoelectronics, lasers, and light-emitting diodes. Through this, there has recently been an increase in the use of halide perovskites (HPs) in resistive switching (RS) devices. However, lead-based (Pb-based) perovskites are notorious for being unstable and harmful to the environment. As a result, lead-free (Pb-free) perovskite alternatives are being investigated in achieving the long-term and sustainable use of RS devices. This work describes the characteristics of Pb-based and Pb-free perovskite RS devices. It also presents the recent advancements of HP RS devices, including the selection strategies of perovskite structures. In terms of resistive qualities, the directions of both HPs appear to be identical. Following that, the possible impact of switching from Pb-based to Pb-free HPs is examined to determine the requirement in RS devices. Finally, this work discusses the opportunities and challenges of HP RS devices in creating a stable, efficient, and sustainable memory storage technology. 2022 American Chemical Society. All rights reserved.